2010
DOI: 10.1177/1474651409355115
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-treated diabetes and driving: what is the patient’s knowledge of current regulations?

Abstract: O ur survey aimed to determine whether educational deficits exist regarding patients' knowledge of current driving regulations. We surveyed 100 insulintreated diabetes patients using questionnaires in October 2008. Fifty-eight were male and 42 female. Mean age was 52.9 years, mean duration of diabetes 15.1 years and mean glycated haemoglobin A 1C 7.5%. Eighty-nine patients (89%) had notified the UK Driver and Vehicle Licensing Agency and 79 (79%) their insurance company of insulin treatment. Sixty-five patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
5
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 11 publications
2
5
0
1
Order By: Relevance
“…Less than half of insulin-treated drivers always adhered to these measures. These findings in a nationwide survey are similar to those of previous smaller local surveys, 2,8,9 and demonstrate the need to ensure that people with diabetes receive education about driving safety and the importance of measuring blood glucose before and during driving ( Table 3).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Less than half of insulin-treated drivers always adhered to these measures. These findings in a nationwide survey are similar to those of previous smaller local surveys, 2,8,9 and demonstrate the need to ensure that people with diabetes receive education about driving safety and the importance of measuring blood glucose before and during driving ( Table 3).…”
Section: Discussionsupporting
confidence: 76%
“…Previous studies have indicated that other barriers may include restrictions on test strip provision, 9 and a feeling that the advice was unreasonable or inconvenient. 3 It is essential that reasons causing reluctance to measure blood glucose are addressed.…”
Section: Discussionmentioning
confidence: 99%
“…They showed that patients' education needs to be improved. 8,9 In another study from the United Kingdom, 117 patients with insulin-treated diabetes and 106 doctors were interviewed. In this country patients are obliged to inform the Driving and Vehicle Licensing Agency if they are on insulin.…”
Section: Discussionmentioning
confidence: 99%
“…Reasons for not regularly performing blood glucose testing before driving include inconvenience and not having access to a blood glucose meter or strips . As recently as 2010, a UK study reported only 65% of insulin using drivers would ‘consider’ blood glucose testing before driving and the mean length of time they would drive before re‐checking their glucose level was 2.8 h . Adequate hypoglycaemic awareness is a pre‐requisite for driving and the expected response on experiencing hypoglycaemic symptoms is to stop, however, many drivers continue to drive .…”
Section: Discussionmentioning
confidence: 99%